Perkembangan Saintifik Ilmu Qawa’id al-Tafsir - Salman Harun (Qur'an and Hadith Academic Society, 2014)
This research compares and discusses the sciences of the Qur’an (‘ulum al-Qur’an) and the sciences of interpretational guidelines (Qawa‘id al-Tafsir), as have been shown in the popular books used in Indonesia – works of al-Zarkashi, al-Suyuti, al-Zarqani and Salih – with that of Khalid ibn ‘Uthman al-Sabt. The later has proposed 280 guidelines and 100 subguidelines, which are relevant as the basis for interpreting the Qur’an. The writer, however, argues that more guidelines are still needed.